Additive Conjunction Functions In Fantasy Narrative: A Cohesive Analysis Of J.R.R. Tolkien's The Hobbit - Ida Bagus Made Sadu Gunawan; Winarta, Ida Bagus Gde Nova (Institut Pariwisata dan Bisnis Internasional, 2026)
This study focused on analyzing the conjunctions, especially additive conjunction and its functions in a novel entitled “The Hobbit” by J. R. R. Tolkien. In this study, Data collection carried out with an observational approach. The data were analyzed by applying qualitative method. The analysis was started by determining the types of conjunction namely additive conjunction in a novel entitled “The Hobbit” by J. R. R. Tolkien. Then, it followed by the analysis of the functions of additive conjunction found in the novel, namely: Simple Additive Relation; or, and, and…to.., Complex Additive Relation (Emphatic); In addition, moreover, furthermore, Complex Additive Relation (De- empathic); By the way, Cooperative Relation; similarly, and Appositive Relation; that is, I mean. Finally, this conjunction has the main function of adding new ideas or facts to a sentence to make it more.